2005
DOI: 10.1128/mcb.25.22.10060-10070.2005
|View full text |Cite|
|
Sign up to set email alerts
|

Insights into the Role of Histone H3 and Histone H4 Core Modifiable Residues in Saccharomyces cerevisiae

Abstract: The biological significance of recently described modifiable residues in the globular core of the bovine nucleosome remains elusive. We have mapped these modification sites onto the Saccharomyces cerevisiae histones and used a genetic approach to probe their potential roles both in heterochromatic regions of the genome and in the DNA repair response. By mutating these residues to mimic their modified and unmodified states, we have generated a total of 39 alleles affecting 14 residues in histones H3 and H4. Rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
213
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(222 citation statements)
references
References 55 publications
9
213
0
Order By: Relevance
“…DNA repair also appears dependent on H3-K115 and/or H3-K122 acetylation. H3-K115Q increases sensitivity to hydroxyurea, whereas H3-K115R does not (23). Moreover, H3-K115A, H3-K122A, and H3-K122Q were all shown to be highly sensitive to Zeocin, a DNA double strand break mimetic (24).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…DNA repair also appears dependent on H3-K115 and/or H3-K122 acetylation. H3-K115Q increases sensitivity to hydroxyurea, whereas H3-K115R does not (23). Moreover, H3-K115A, H3-K122A, and H3-K122Q were all shown to be highly sensitive to Zeocin, a DNA double strand break mimetic (24).…”
mentioning
confidence: 97%
“…H3-K115R, which mimics constitutively unacetylated lysine, exhibits wild type silencing in both regions. However, H3-K122R exhibits wild type silencing in ribosomal DNA but reduced silencing in telomeres (23). Another study showed that H3-K115A and H3-K122A separately displayed reduced expression of the PHO5 gene in budding yeast, whereas H3-K122A exhibited wild type expression (24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Six independent research groups recently reported the discovery of lysine 56 as a novel site of histone H3 acetylation in the budding yeast Saccharomyces cerevisiae. [3][4][5][6][7][8] K56 acetylation has also been observed in the fission yeast Schizosaccharomyces pombe, 6 which is evolutionarily very distant from S. cerevisiae. 9 Based on mass spectrometry, K56 acetylation occurs in Plasmodium falciparum (A. Salcedo and H. Stunnenberg, in preparation) and the modification has also been reported in Drosophila.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in eukaryotic genetic model organisms, like Saccharomyces cerevisiae, a model that allows for direct mutations of histones in vivo, the majority of histone N-terminal tail point mutants have been demonstrated to be completely viable despite apparent evolutionary pressures to conserve near-invariant histone amino-acid sequences (Hyland et al, 2005;Dai et al, 2008). Although specific core amino acids located at the H3/H4 histone-fold motif have been shown to be important for aspects of transcriptional silencing in yeast (this core is centered around lysine 79 of H3 and may be important to nucleosomal stability) (Park et al, 2002), these data indicate a high level of functional redundancy in histone modifications that must be considered.…”
Section: Reconciling the Dangers Of Hyper-enthusiasm With Cautious Inmentioning
confidence: 99%